Dietary intakes in geriatric orthopaedic rehabilitation patients: Need to look at food consumption not just provision. Issue 4 (August 2016) - Bannerman, Elaine; Cantwell, Linda; Gaff, Lisa; Conroy, Aishling; Davidson, Isobel; Jones, Jacklyn
Summary: Background & aims: Elderly orthopaedic rehabilitation patients are potentially at high nutritional risk and thus nutrition provision is a fundamental component of the multidisciplinary care to optimise physical rehabilitation. Hospital food service (catering) is internationally recognised as a key component of good clinical care of patients and has the potential to provide a population approach to managing under-nutrition. Within Scotland, there have been significant developments with regards to food, fluid and nutritional care within clinical settings including the setting of clinical standards. However audits to date have focused on processes being in place and not patient outcomes. Therefore, this study aimed to evaluate food provision and consumption in elderly orthopaedic rehabilitation settings to determine whether nutrition standards are being met. Methods: A service evaluation of food provision and consumption to inpatients 65 years and older in post-acute geriatric orthopaedic wards over 24 h in National Health Service (NHS) hospitals in Scotland, UK was conducted. Food provision from each meal, in-between meal snacks from the trolley service and also on ward provisions were measured by weighing all items prior to being served to the patient. Any leftover food items were also weighed to allow the amount of food consumed to be determined. Estimated energy and protein contents of foods provided and consumed were compared against nutrient standards for hospital foods. Results: Food provision to n = 175 patients, across seven wards and three hospitals was significantly less than standards set for energy and protein provision for 'nutritionally well' patients; (Hospital B mean diff – 549 kcals, −19 g p < 0.01; and Hospital C mean diff −250 kcals, −12 g, p < 0.001). Patients consumed approximately three quarters (74%) of the food they were provided. Higher provision of both energy and protein was associated with higher levels of consumption (r = 0.77 and r = 0.79, p < 0.001), respectively. Conclusion: Significant work has been undertaken to improve the nutritional care of patients in hospitals. However, at a time where inefficiencies in clinical services must be reduced along side improvements in patient outcomes, there is a need for greater monitoring of patient food intakes to enable improvements in food production and food service systems to this end.